PENGARUH STRATEGI PROMOSI, CITRA MERK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI GUYUB RUKUN MART BANJARMANGU, BANJARNEGARA - Ratna Suryani; Gustio Bayu Adhitama (Medikonis, 2021)
ABSTRACT The problems experienced by Guyub Rukun Mart is the lack of a promotional strategy carried out and the lack of promotion carried out by Guyub Rukun Mart, so that the general public still doesn't know about it. This is because the Guyub Rukun Mart is not an economist, plus the Guyub Rukun Mart brand image. Marts that are not well known to the wider community and the quality of the products sold do not all have the quality that is in accordance with the wishes of the community. This study aims to determine the effect of promotional strategies, brand image and product quality on purchasing decisions. In this study, researchers used quantitative methods. The data source used is primary data. The sampling technique used random sampling technique. The data was collected by using a questionnaire distributed directly to buyers as many as 98 respondents. Data analysis in this study used multiple linear regression analysis with SPSS version 24. The results of this study indicate that promotional strategies and product quality affect purchasing decisions, while brand image does not affect purchasing decisions but jointly promotional strategies, brand image and product quality affect purchasing decisions.